2021
DOI: 10.1108/aea-07-2020-0088
|View full text |Cite
|
Sign up to set email alerts
|

Impact of socioeconomic development on inflation in South Asia: evidence from panel cointegration analysis

Abstract: Purpose This study aims to examine the influence of socioeconomic development on inflation in South Asia using the foreign exchange rate and money supply as control variables. Design/methodology/approach The study uses annual panel data for five South Asian economies, namely, Bangladesh, India, Nepal, Pakistan and Sri Lanka over the period 1990–2018, applies cointegrating regression techniques, namely, the panel dynamic ordinary least square (OLS) and fully modified OLS estimators to examine the long-run rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
2
2
0
2
Order By: Relevance
“…Therefore, the money supply must be controlled in order not to create an inflationary environment ( Musgrave and , 1989). The empirical results regarding the positive effect of money supply on inflation are consistent with the findings of Moroney (2002), Nguyen (2015), Sharma and Nurudeen (2019) and Islam (2021).…”
Section: Results Of Panel Fmols and Dolssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, the money supply must be controlled in order not to create an inflationary environment ( Musgrave and , 1989). The empirical results regarding the positive effect of money supply on inflation are consistent with the findings of Moroney (2002), Nguyen (2015), Sharma and Nurudeen (2019) and Islam (2021).…”
Section: Results Of Panel Fmols and Dolssupporting
confidence: 86%
“…Empirical findings showed that money supply (M1) has a positive effect on inflation. Islam (2021) analysed the impact of socioeconomic development on inflation in South Asia with DOLS, FMOLS and the Toda-Yamamoto Granger causality test over the period 1990-2018. According to the results obtained, broad money supply has the usual positive impact on domestic inflation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dengan meningkatnya pembangunan manusia yang tercermin dari manusia yang sehat, terdidik, dan sejahtera, meningkat pula permintaan dari masyarakat, yang pada akhirnya akan menciptakan inflasi. Salah satu penelitian terbaru yang meneliti pengaruh aspek sosial ekonomi (yang tercermin dari IPM) pada inflasi dilakukan oleh Islam (2021) yang melingkupi negaranegara di Asia Selatan.…”
Section: Indeks Pembangunan Manusia (Ipm)unclassified
“…Alat analisis yang dipakai pada penelitian kali ini yaitu analisis regresi Ordinary Least Square (OLS), dengan menggunakan model ekonometrik seperti di bawah ini: Model ekonometrik di atas merupakan kombinasi dari model ekonometrik Santosa (2017), Utami & Soebagiyo (2013), Nguyen et al (2012), Gyebi & Boafo (2013), Islam (2021), dan Perlambang (2017). Tingkat suku bunga, pengeluaran pemerintah, konsumsi, keseluruhan uang beredar, serta nilai tukar dihipotesiskan akan memiliki dampak baik pada inflasi.…”
Section: Metodeunclassified